Percutaneous sacroplasty using CT guidance for pain palliation in sacral insufficiency fractures. (23rd January 2013) - Dougherty, Ryne W; McDonald, Jennifer S; Cho, Yong Woon; Wald, John T; Thielen, Kent R; Kallmes, David F
Abstract : Background and objective: Sacroplasty has emerged as a treatment option for patients with painful osteoporotic sacral insufficiency fractures. We report short-term outcomes in a consecutive cohort of patients treated with sacroplasty. Methods: We retrospectively reviewed 57 patients treated with sacroplasty for painful osteoporotic sacral fractures at our institution between 2004 and 2011. An 11-point numerical rating scale pain score was recorded at rest and at activity pre- and post-procedure. Opioids prescribed to the patient both pre- and post-procedure were recorded. Results: Mean duration of pain prior to sacroplasty was 3 weeks (IQR 2–5). Procedural complications were minimal. Median post-procedure follow-up time was 2.5 weeks (IQR 1–5) among 45 patients with available data. Thirty-seven (82%) of the 45 patients experienced a numerical or descriptive decrease from initial pain at follow-up. Median activity pain scores collected from 13 patients decreased from 10 (IQR 8.5–10) pre-procedure to 6 (IQR 4–6.8) post-procedure (p<0.0001), and median rest pain scores collected from 29 patients decreased from 7 (IQR 4–8.5) to 2 (IQR 1–3.5)(p<0.0001). Twenty-two (76%) of 29 patients had at least a 30% decrease in rest pain scores. The median number of opioids prescribed per patient decreased from 1 (IQR 1–2) pre-procedure to 0 (IQR 0–1) post-procedure (p<0.0001). Thirty-four of 57 patients (60%) had decreased opioid usage, 15 (26%) patients had unchanged usage and 8 (14%) had increased usage. Conclusions: Our series demonstrates that sacroplasty is a safe and effective treatment in patients with painful osteoporotic insufficiency fractures.